2018
DOI: 10.1038/s41467-018-06317-8
|View full text |Cite
|
Sign up to set email alerts
|

Gas-solid reaction based over one-micrometer thick stable perovskite films for efficient solar cells and modules

Abstract: Besides high efficiency, the stability and reproducibility of perovskite solar cells (PSCs) are also key for their commercialization. Herein, we report a simple perovskite formation method to fabricate perovskite films with thickness over 1 μm in ambient condition on the basis of the fast gas−solid reaction of chlorine-incorporated hydrogen lead triiodide and methylamine gas. The resultant thick and smooth chlorine-incorporated perovskite films exhibit full coverage, improved crystallinity, low surface roughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 71 publications
4
121
0
Order By: Relevance
“…These differences were reflected to the photoluminescence lifetimes, which increased from 55 (without MACl) to 316 ns for the 5% MACl films (Figure 2a). [45] The two-step conversion concept proved to be valid also when the second step in two-step spin-coating was replaced from immersion to spin-coating of MAI/MACl solution in 2-propanol (the method was called interdiffusion). [43] The method seemed to similarly work also for mesoporous titania substrates and when MACl was added Maria Konstantakou is a post-doc research assistant in the group of Prof. Stergiopoulos at the Aristotle University of Thessaloniki.…”
Section: Two-step Conversionmentioning
confidence: 99%
“…These differences were reflected to the photoluminescence lifetimes, which increased from 55 (without MACl) to 316 ns for the 5% MACl films (Figure 2a). [45] The two-step conversion concept proved to be valid also when the second step in two-step spin-coating was replaced from immersion to spin-coating of MAI/MACl solution in 2-propanol (the method was called interdiffusion). [43] The method seemed to similarly work also for mesoporous titania substrates and when MACl was added Maria Konstantakou is a post-doc research assistant in the group of Prof. Stergiopoulos at the Aristotle University of Thessaloniki.…”
Section: Two-step Conversionmentioning
confidence: 99%
“…Additionally, sequential deposition can be used in conjunction with solution processing, whereby one precursor layer is evaporated (typically the metal halide), with the other precursor layer (usually the precursor containing the organic cation) subsequently being deposited via spin/dipcoating . While this combination of dry and wet techniques shows some promise, extended annealing times are required to evaporate residual solvents, and there is little control over film thickness, rendering this process inadequate for upscaling of perovskite tandem devices . Therefore, considering all requirements, coevaporation appears to be the ideal fabrication method for the deposition of both small and large‐scale perovskite thin films, particularly those which are to be incorporated into two‐terminal multijunction PV devices.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Liu et al demonstrated that incorporation of MACl into the HPbI 3 film improves the crystallinity and uniformity of the resulting perovskite films, enabling over 1 µm thick perovskite films with reduced trap density and enhanced mobility. Using the perovskite films, they demonstrated peak PCEs of 20.0% and 15.3% for the cell and module with active area of 0.1 cm 2 and 5 cm × 5 cm, respectively …”
Section: Large‐area Fabrication Methods For Perovskite Filmsmentioning
confidence: 99%